The archaeology of consumer culture - Mullins, Paul R., 1962- (American experience in archaeological perspective., 2011)
Americans have long identified themselves with material goods. In this study, Paul Mullins sifts through this continent's historical archaeological record to trace the evolution of North American consumer culture.